2008
DOI: 10.1111/j.1365-246x.2007.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of Iraq from receiver functions and surface wave dispersion: implications for understanding the deformation history of the Arabian-Eurasian collision

Abstract: S U M M A R YWe report the crustal structure for two locations in Iraq estimated by joint inversion of P-wave receiver functions (RFs) and surface (Rayleigh) wave group velocity dispersion. RFs were computed from teleseismic recordings at two temporary broad-band seismic stations located in Mosul (MSL) in the Zagros Fold Belt and Baghdad (BHD) in the Mesopotamian Foredeep. Group velocity dispersion curves at the sites were derived from continental-scale tomography. The inversion results show that the crustal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Our crustal model along transect A-A shows a crustal thickness of 42-43 km below the Arabian Foreland Basin, gradually increasing towards the Zagros Mountains. These values are similar to those proposed by Gök et al (2008) and Nasrabadi et al (2008). Maximum crustal thicknesses are obtained beneath the SSZ (55 km) and the Alborz Mountains (53 km) in good agreement with Paul et al (2010) and Nasrabadi et al (2008).…”
Section: Crustal Geometrysupporting
confidence: 92%
See 3 more Smart Citations
“…Our crustal model along transect A-A shows a crustal thickness of 42-43 km below the Arabian Foreland Basin, gradually increasing towards the Zagros Mountains. These values are similar to those proposed by Gök et al (2008) and Nasrabadi et al (2008). Maximum crustal thicknesses are obtained beneath the SSZ (55 km) and the Alborz Mountains (53 km) in good agreement with Paul et al (2010) and Nasrabadi et al (2008).…”
Section: Crustal Geometrysupporting
confidence: 92%
“…in the Alborz along A-A profile, in the UDMA and IZ along the B-B profile). In general, along both transects, our resulting Moho depth values are consistent with the results from Gök et al (2008), which found ∼42-45 km of crustal thickness in the Foreland Basin, from Gritto et al (2008), which calculated Moho depth values between 44 and 52 km in the NW Zagros, and from Radjaee et al (2010), which found ∼55 km below the Zagros Mountains and 53-58 km below the Alborz Mountains. Our values of Moho depth differ slightly from those proposed by Jimenez-Munt et al (2012), being 3-5 km higher along profile A-A (Fig.…”
Section: Crustal Geometrysupporting
confidence: 90%
See 2 more Smart Citations
“…Amplitudes from phase conversions can be enhanced by deconvolving the vertical component, where P-waves dominate, from the radial component, where the SV-waves resulting from the conversions are prominent. Source and instrument effects are conveniently eliminated in the process (e.g., Gök et al, 2008). The deconvolution process is often performed by spectral division.…”
Section: Computation Of Rfsmentioning
confidence: 99%